SISTEM PENDUKUNG KEPUTUSAN BIBIT SAPI UNGGUL DENGAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEB - Ivan Filbert; Dedi Trisnawarman; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
The purpose of this study is to develop a Decision Support System for Selection of superior beef cattle based on criteria with existing parameters. There are five criteria used in this study, namely Weight, Height, Age, Price, and Feed Consumption. These criteria were obtained from the results of interviews with Mutiara Halim Trading Business and a literature study that had been conducted. The method used is the Simple Additive Weighting (SAW) method. The result obtained is a Decision Support System that can be accessed by the Admin and User to select the desired cow. The program is run by using XAMPP as Localhost and PHPMyAdmin as Database. Based on the trials that have been carried out, it can be concluded that the system created can be run and can assist the User in making decisions to determine superior cow breeds